2022
DOI: 10.1002/anie.202201166
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Changes the Local Electron Densities of Nickel 3d Orbitals for Efficient Electrocatalytic CO2 Reduction

Abstract: Generally, in terms of electrocatalytic CO2 reduction, single‐atom catalysts show high selectivities yet low current densities whereas conventional nanoparticle catalysts exhibit relatively high current densities but low selectivities. This work combines the advantages of the two classes of catalysts by constructing a Ni‐Gd‐N‐doped carbon black electrocatalyst within which NiI active sites are exposed outside the carbon layers and Ni nanoparticles are encapsulated inside the carbon layers. The Gd atoms can not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 61 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…Lanthanide metals (LMs) have attracted special interest as dopants in catalysis. 21−24 The distinctive electronic structure of 4f electrons and the unfilled 5d orbital endow LMs with intense spin−orbit coupling and lanthanide contraction effects, 25,26…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanide metals (LMs) have attracted special interest as dopants in catalysis. 21−24 The distinctive electronic structure of 4f electrons and the unfilled 5d orbital endow LMs with intense spin−orbit coupling and lanthanide contraction effects, 25,26…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide metals (LMs) have attracted special interest as dopants in catalysis. The distinctive electronic structure of 4f electrons and the unfilled 5d orbital endow LMs with intense spin–orbit coupling and lanthanide contraction effects, , which can effectively adjust local electron densities of the surrounding atoms, and keep the surrounding atoms in a high-valence chemical state. This provides a possibility of stabilizing the Cu + species in CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) images further demonstrated that the nanoparticle structure of the MoO 3 /Ni-N-C sample (inset in Figure c). The HRTEM image also showed two sets of lattice spacings of 0.203, 0.232, and 0.198 nm (Figure d), corresponding to the crystalline planes of Ni(111), MoO 3 (131), and MoO 3 (160), suggesting that the two types of nanoparticles were embedded in the surface carbon layer lattice . Moreover, the corresponding X-ray spectroscopy (EDX) mapping results (Figures e–i) show that the elements of Ni and Mo are regularly scattered along the surface of the carbon layer .…”
Section: Resultsmentioning
confidence: 91%
“…The HRTEM image also showed two sets of lattice spacings of 0.203, 0.232, and 0.198 nm (Figure 1d), corresponding to the crystalline planes of Ni(111), MoO 3 (131), and MoO 3 (160), suggesting that the two types of nanoparticles were embedded in the surface carbon layer lattice. 27 Moreover, the corresponding Xray spectroscopy (EDX) mapping results (Figures 1e−i S1, Supporting Information). 29,30 Raman spectra show two similar Raman peaks for each sample in Figure 2b, the D peak (1352 cm −1 ) and G peak (1589 cm −1 ), indicating disordered carbon and graphitic carbon, respectively, 31,32 where the I D /I G values of MoO 3 /Ni-N-C is considerably larger than Ni-N-C, which means that the carbon layer structure has been changed by the presence of MoO 3 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, this activity outperformed the reported state-of-the-art rare earth metal–N–C catalysts, such as Y/NC (1.2 mA cm –2 ), Pr-NC (0.9 mA cm –2 ), and so forth. , These results suggested that only one tenth amount of the rare metal was required to loading on the ultrapolar supports to show a more superior CO 2 reduction performance. By comparison with the state-of-the-art precious metal and rare earth metal-based electrocatalysts in the literature, the CO 2 RR activities for introducing metals into UPC were also outstanding, which benefits from simultaneous enhancements of metal utilization and its accessibility (Figure d). Considering these unique benefits, the systematic study of this strategy in developing advanced precious metals-doped ultrapolar carbons as catalysts for heterogeneous reactions is in progress.…”
Section: Resultsmentioning
confidence: 99%